Optimization of the Microstructure and Mechanical Properties of a Laves Phase-Strengthened Hypoeutectic NiAl/Cr(Mo,W) Alloy by Suction Casting - Sheng, L.Y.; Du, B.; Zan, S.P.; Lai, C.; Jiao, J.K.; Gao, Y.B.; Xi, T.F. (Проблемы прочности, 2018)
A niobium (Nb)-doped NiAl/Cr(Mo,W) hypoeutectic alloy was prepared by conventional and suction casting methods. Its microstructure and compression properties were studied to evaluate the effect of a manufacturing process. A coarse primary NiAl phase and NiAl/Cr(Mo) eutectic cell are demonstrated to be the main components of a NiAl/Cr(Mo,W)–Nb hypoeutectic alloy. Отримано легований ніобієм (Nb) доевтектичний сплав NiAl/Cr(Mo,W) при звичайному литті і литті методом вакуумного всмоктування. Вивчено його мікроструктура і механічні властивості при стиску для оцінки впливу процесу виробництва. Показано, що велика первинна фаза NiAl і евтектична комірка NiAl/Cr(Mo) є основними компонентами сплаву NiAl/Cr(Mo,W) Nb. Получен легированный ниобием (Nb) доэвтектический сплав NiAl/Cr(Mo,W) обычным литьем и литьем методом вакуумного всасывания. Изучены его микроструктура и механические свойства при сжатии для оценки влияния процесса производства. Показано, что крупная первичная фаза NiAl и эвтектическая ячейка NiAl/Cr(Mo) являются основными компонентами сплава NiAl/Cr(Mo,W) Nb.